A lithium battery separator and preparation method thereof
By adopting the structure of the framework fiber layer, nanofiber layer and polymer network layer in the lithium battery separator and forming micropores through liquid-liquid phase conversion, the problem of low porosity of the existing lithium battery separator is solved, and the electrolyte wetting ability and the comprehensive performance of the battery are significantly improved.
Patent Information
- Application Number
- CN201911416124.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2039-12-31
AI Technical Summary
The existing lithium battery separators have low porosity, poor thermal dimensional stability, and poor electrolyte wetting, which affect the battery capacity, circulation performance and safety.
A lithium battery separator composed of a skeleton fiber layer, a nanofiber layer and a polymer network layer is used to form the base film by paper-like method, and oil-phase polymer is sprayed on the surface of the base film to form micropores through liquid-liquid phase conversion to improve porosity.
The porosity, breathability and electrolyte wetting properties of the lithium battery separator are significantly improved, the long circulation performance and safety of the battery are improved, the standstill time of the battery cell after injection is shortened, and the production efficiency is improved.
Smart Images

Figure CN110993868B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium battery separator and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are mainly composed of four major materials: positive electrode materials, negative electrode materials, electrolytes, and diaphragms. The diaphragm is the key component related to the safety of lithium batteries. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle, and safety performance. A diaphragm with excellent performance plays an important role in improving the overall performance of the battery. The main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through.
[0003] At present, lithium battery separators are basically polyolefin separators and separators with ceramic functional coating on the surface of polyolefin separators. These separators have low heat resistance, poor thermal dimensional stability and poor electrolyte wettability. Summary of the invention
[0004] In order to overcome the deficiencies of the prior art, an object of the present invention is to provide a lithium battery separator and a preparation method thereof, which can improve the porosity of the separator.
[0005] To achieve the above-mentioned purpose, the technical solution of the present invention is a lithium battery separator, which is formed by stacking a skeleton fiber layer, a nanofiber layer and a polymer network layer from bottom to top; the skeleton fiber layer is interwoven with micron fibers and chemical short fibers, the nanofiber layer is interwoven with nanofibers, and the polymer network layer is interwoven with polymers; the nanofiber portion extends into the skeleton fiber layer, and the polymer portion extends into the nanofiber layer.
[0006] Furthermore, the diameter of the nanofiber is 5-100 nm; the diameter of the micron fiber is 0.5-1 μm, and the length is 10-1000 μm; the diameter of the chemical short fiber is 1-6 μm, and the length is 1-12 mm.
[0007] Furthermore, the nanofiber is at least one of nano-aramid fiber, nano-cellulose fiber, nano-polyacrylonitrile fiber, and fibrillated Tencel fiber; the micron fiber is at least one of fibrillated chemical staple fiber, pulp, and micron cellulose fiber; the pulp can be wood pulp, cotton pulp, aramid pulp, polyethylene pulp, etc.; the chemical staple fiber is at least one of PET fiber, PAN fiber, PBO fiber, PA fiber, PI fiber, and aramid staple fiber.
[0008] Furthermore, the polymer is at least one of aramid, polyacrylonitrile, polyvinylidene fluoride, and polymethyl methacrylate.
[0009] Furthermore, the lithium battery separator has a thickness of 10-70 μm, a porosity of 45-75%, an air permeability of <50s / 100cc, and a mechanical strength of 10-100Mpa.
[0010] The present invention also provides a method for preparing the above-mentioned lithium battery separator, comprising the following steps:
[0011] 1) Add water and dispersant to disperse the micron fiber and chemical short fiber evenly to obtain skeleton fiber slurry, which is then molded into a skeleton fiber layer;
[0012] 2) adding water and dispersant to disperse the nanofibers evenly to obtain nanofiber slurry; then depositing the nanofiber slurry on the skeleton fiber layer to form a nanofiber layer, and obtaining a wet film after filtering and squeezing;
[0013] 3) The polymer and the organic solvent are mixed and stirred evenly to obtain an oil phase polymer solution; the oil phase polymer solution is sprayed onto the surface of the nanofiber layer of the wet film, the organic solvent quickly leaves and dissolves with water, the polymer precipitates into a network, and a polymer network layer is formed on the surface of the wet film, which is then sent to an oven for baking to volatilize the organic solvent and water to obtain a lithium battery separator.
[0014] Furthermore, in step 2), the membrane is filtered and squeezed until the moisture content is 35-80%, and then transferred to a dry blanket to obtain a wet membrane.
[0015] Furthermore, the ratio of the sum of the amounts of the micron fibers and the chemical short fibers, the amount of the nanofibers, the amount of the polymer and the dispersant is 30-70:20-80:1-20:0.1-2.
[0016] Furthermore, in step 3), the content of the polymer in the oil phase polymer solution is 10-30%.
[0017] Furthermore, the dispersant is any one of sodium carboxymethyl cellulose, polyacrylamide, polyethylene oxide, and sodium hexametaphosphate; and the organic solvent is any one of NMP, acetone, tetrahydrofuran, DMF, DMA, TEP, DMSO, DMAc, and butanol sulfone.
[0018] The principle of the present invention is as follows:
[0019] The present invention adopts a one-time molding method to form a lithium battery separator. The skeleton fibers (micron fibers and chemical short fibers) and nanofibers are formed into a base membrane by a papermaking method. The base membrane has a rich pore structure, but there are still macropores on the surface of the base membrane. Then, an oil phase polymer is sprayed to form micropores at the macropores and on the surface of the base membrane through liquid-liquid phase conversion, thereby re-forming pores, increasing porosity, and improving electrolyte wettability.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The lithium battery separator provided by the present invention has high porosity, good air permeability, good liquid absorption, good electrolyte retention, and significant improvement on the long cycle of the battery. It has instant liquid absorption and can activate the battery after 10 seconds of injection. It has good electrolyte infiltration performance and can shorten the standing time of the battery cell after injection. It has good thermal dimensional stability and can shorten the baking time of the separator. The use of the separator provided by the present invention can improve the production efficiency of the battery, and has excellent electrochemical performance and good safety performance.
[0022] (2) The main fiber used in the lithium battery separator provided by the present invention is resistant to high temperatures and chemically stable. The prepared separator has good thermal dimensional stability, and the separator surface also has abundant functional groups, which has a good capture effect on metal ions and can inhibit the formation of lithium dendrites.
[0023] (3) The present invention forms a base membrane by knotting nanofibers and skeleton fibers. The chemical bonds and intermolecular forces between the nanofibers provide good strength for the diaphragm. The fibers overlap each other to form a rich pore structure with good heat resistance. Then, pores are formed again at the macropores and on the surface by liquid-liquid phase conversion to increase the porosity. A one-time molding method is adopted. The solvent in the preparation process of the non-woven base membrane is the water phase. Then, an oil phase polymer is sprayed on the surface of the wet membrane. The organic solvent leaves and dissolves with water. The polymer precipitates into a network to form a polymer network layer.
[0024] (4) The polymer network layer on the surface of the lithium battery separator provided by the present invention has good adhesion to the electrode plate, thereby preventing slippage between the separator and the electrode plate. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 A schematic diagram of the structure of a lithium battery separator provided in Example 1 of the present invention;
[0027] Figure 2 A scanning electron microscope image of a lithium battery separator obtained by preparing a wet film by using steps 1) and 2) of the preparation method provided in Example 1 of the present invention and then baking, curling, post-processing, finishing and slitting;
[0028] Figure 3This is a scanning electron microscope image of the lithium battery separator provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] like Figure 1 As shown, this embodiment provides a lithium battery separator, which is formed by stacking a skeleton fiber layer, a nanofiber layer and a polymer network layer from bottom to top; wherein the skeleton fiber layer is interwoven with de-filamentized PAN fibers and PET fibers, the nanofiber layer is interwoven with nano-aramid fibers and nano-cellulose fibers, and the polymer network layer is interwoven with PVDF; and the nano-aramid fibers and nano-cellulose fibers partially extend into the skeleton fiber layer, and the PVDF partially extends into the nanofiber layer.
[0032] The preparation method of the above-mentioned lithium battery separator comprises the following steps:
[0033] 1) Add water and sodium hexametaphosphate to 50 parts of PAN fibers and PET fibers mixed in any proportion to disperse and evenly disperse them to obtain a skeleton fiber slurry, which is deposited and formed to form a skeleton fiber layer;
[0034] 2) adding water and sodium hexametaphosphate to 10 parts of nano-aramid fibers and 40 parts of nano-cellulose fibers to disperse them uniformly to obtain nano-fiber slurry; then depositing the nano-fiber slurry on the skeleton fiber layer to form a nano-fiber layer, filtering and squeezing until the moisture content of the membrane is 60%, and then transferring it to a dry blanket to obtain a wet membrane;
[0035] 3) 20 parts of PVDF and NMP solvent are mixed and stirred evenly to obtain an oil phase polymer solution, in which the content of polymer is 20%; the oil phase polymer solution is sprayed onto the surface of the nanofiber layer of the wet film, NMP quickly leaves and dissolves in water, the polymer precipitates into a network, pores are formed at the macropores and surface of the membrane, and a polymer network layer is formed on the surface of the wet film, which is then sent to an oven for baking to volatilize the organic solvent and water, and the lithium battery separator is obtained after curling, post-processing, finishing and slitting.
[0036] In the method of this embodiment: the total amount of sodium hexametaphosphate used in step 1) and step 2) is 1.5 parts.
[0037] The wet film is prepared by using step 1) and step 2) of the above preparation method and then baked, rolled, post-processed, trimmed and cut. The scanning electron microscope image of the obtained lithium battery separator is as follows: Figure 2 As shown, the scanning electron microscope image of the lithium battery separator prepared by the above method is as follows Figure 3 As shown, it can be seen that the surface of the diaphragm obtained by forming the skeleton fibers (micron fibers and chemical short fibers) and nanofibers using a papermaking method still has macropores, while the preparation method of the present invention is based on steps 1) and 2) and is sprayed with an oil phase polymer to form micropores at the macropores and on the surface of the base membrane through liquid-liquid phase conversion, thereby increasing the porosity of the diaphragm surface.
[0038] The diameter of the nano-aramid fiber and nano-cellulose fiber used in the lithium battery separator and its preparation method of this embodiment is 5-100nm; the diameter of the fibrillated PAN fiber is 0.5-1μm, and the length is 10-1000 microns; the diameter of the PET fiber is 2μm, and the length is 5 mm; the thickness of the prepared lithium battery separator is 25μm, the porosity is 65%, the air permeability is 13s / 100cc, and the mechanical strength is 37Mpa.
[0039] Example 2
[0040] The present embodiment provides a lithium battery separator, which is formed by stacking a skeleton fiber layer, a nanofiber layer and a polymer network layer from bottom to top; wherein the skeleton fiber layer is interwoven with PAN fibers, PET fibers and de-filamentized PAN fibers, the nanofiber layer is interwoven with nanocellulose fibers, and the polymer network layer is interwoven with polyacrylonitrile and polyvinylidene fluoride; and the nanocellulose fibers partially extend into the skeleton fiber layer, and the polyacrylonitrile and polyvinylidene fluoride partially extend into the nanofiber layer.
[0041] The preparation method of the above-mentioned lithium battery separator comprises the following steps:
[0042] 1) Add water and polyacrylamide to 40 parts of PAN fiber, PET fiber and PAN fiber mixed in any proportion to disperse them evenly to obtain a skeleton fiber slurry, which is deposited and formed to form a skeleton fiber layer;
[0043] 2) adding water and polyacrylamide to 60 parts of nanocellulose fibers to disperse them uniformly to obtain nanofiber slurry; then depositing the nanofiber slurry on the skeleton fiber layer to form a nanofiber layer, filtering and squeezing until the moisture content of the membrane is 70%, and then transferring it to a dry blanket to obtain a wet membrane;
[0044] 3) 10 parts of polyacrylonitrile, polyvinylidene fluoride and DMSO solvent mixed in any proportion are mixed and stirred evenly to obtain an oil phase polymer solution, in which the content of polymer is 20%; the oil phase polymer solution is sprayed onto the surface of the nanofiber layer of the wet film, DMSO quickly leaves and dissolves in water, the polymer precipitates into a network, pores are formed at the macropores and surface of the membrane, a polymer network layer is formed on the surface of the wet film, and then it is sent to an oven for baking to volatilize the organic solvent and water, and the lithium battery separator is obtained after curling, post-treatment, finishing and slitting.
[0045] In the method of this embodiment, the total amount of polyacrylamide used in step 1) and step 2) is 0.5 parts.
[0046] The diameter of the nanocellulose fibers used in the lithium battery separator and the preparation method thereof of this embodiment is 5-100nm; the diameter of the fibrillated PAN fibers is 0.5-1μm, and the length is 10-1000 microns; the diameter of the PAN fibers and the PET fibers is 4μm, and the length is 3 mm; the thickness of the prepared lithium battery separator is 20μm, the porosity is 65%, the air permeability is 11s / 100cc, and the mechanical strength is 45Mpa.
[0047] Example 3
[0048] The present embodiment provides a lithium battery separator, which is formed by stacking a skeleton fiber layer, a nanofiber layer and a polymer network layer from bottom to top; wherein the skeleton fiber layer is interwoven with fibrillated wood pulp, fibrillated PBO microfibers and PET fibers, the nanofiber layer is interwoven with nanocellulose fibers and fibrillated Tencel fibers, and the polymer network layer is interwoven with polyacrylonitrile; and the nanocellulose fibers and fibrillated Tencel fibers partially extend into the skeleton fiber layer, and the polyacrylonitrile partially extends into the nanofiber layer.
[0049] The preparation method of the above-mentioned lithium battery separator comprises the following steps:
[0050] 1) Add water and sodium carboxymethyl cellulose to 30 parts of filamentized wood pulp, filamentized PBO fiber and PET fiber mixed in any proportion to disperse and evenly obtain skeleton fiber slurry, which is deposited and formed to form a skeleton fiber layer;
[0051] 2) adding water and sodium carboxymethyl cellulose to 70 parts of nanocellulose fibers and fibrillated tencel fibers mixed in any proportion to obtain nanofiber slurry; then depositing the nanofiber slurry on the skeleton fiber layer to form a nanofiber layer, filtering and squeezing until the moisture content of the membrane is 40%, and then transferring it to a dry blanket to obtain a wet membrane;
[0052] 3) 10 parts of polyacrylonitrile and DMF solvent are mixed and stirred evenly to obtain an oil phase polymer solution, in which the polymer content in the oil phase polymer solution is 10%; the oil phase polymer solution is sprayed onto the surface of the nanofiber layer of the wet membrane, DMF quickly leaves and dissolves in water, the polymer precipitates into a network, pores are formed at the macropores and surface of the membrane, and a polymer network layer is formed on the surface of the wet membrane, which is then sent to an oven for baking to volatilize the organic solvent and water, and the lithium battery separator is obtained after curling, post-processing, finishing and slitting.
[0053] In the method of this embodiment, the total amount of sodium carboxymethyl cellulose used in step 1) and step 2) is 1 part.
[0054] The diameter of the nanocellulose fiber and fibrillated Tencel fiber used in the lithium battery separator and preparation method of this embodiment is 5-100nm; the diameter of the wood pulp pulp and the fibrillated PBO microfiber is 0.5-1μm, and the length is 10-1000 microns; the diameter of the PET fiber is 5μm, and the length is 6 mm; the thickness of the prepared lithium battery separator is 30μm, the porosity is 70%, the air permeability is 20s / 100cc, and the mechanical strength is 50Mpa.
[0055] Example 4
[0056] The present embodiment provides a lithium battery separator, which is formed by stacking a skeleton fiber layer, a nanofiber layer and a polymer network layer from bottom to top; wherein the skeleton fiber layer is interwoven with aramid pulp and fibrillated PAN fibers and PI fibers, the nanofiber layer is interwoven with nanocellulose fibers, and the polymer network layer is interwoven with polyvinylidene fluoride; and the nanocellulose fibers partially extend into the skeleton fiber layer, and the polyvinylidene fluoride partially extends into the nanofiber layer.
[0057] The preparation method of the above-mentioned lithium battery separator comprises the following steps:
[0058] 1) Add water and sodium hexametaphosphate to 30 parts of aramid pulp and PAN fiber and PI fiber mixed in any proportion to disperse and evenly disperse them to obtain a skeleton fiber slurry, which is deposited and formed to form a skeleton fiber layer;
[0059] 2) adding water and sodium hexametaphosphate to 80 parts of nanocellulose fibers to disperse them uniformly to obtain nanofiber slurry; then depositing the nanofiber slurry on the skeleton fiber layer to form a nanofiber layer, filtering and squeezing until the moisture content of the membrane is 80%, and then transferring it to a dry blanket to obtain a wet membrane;
[0060] 3) Mix 1 part of polyvinylidene fluoride and NMP solvent and stir evenly to obtain an oil phase polymer solution, in which the polymer content is 30%; spray the oil phase polymer solution onto the surface of the nanofiber layer of the wet film, NMP quickly leaves and dissolves in water, the polymer precipitates into a network, pores are formed at the macropores and surface of the membrane, and a polymer network layer is formed on the surface of the wet film, which is then sent to an oven for baking to volatilize the organic solvent and water, and the lithium battery separator is obtained after curling, post-processing, finishing and slitting.
[0061] In the method of this embodiment, the total amount of sodium hexametaphosphate used in step 1) and step 2) is 2 parts.
[0062] The diameter of the nanocellulose fibers used in the lithium battery separator and preparation method thereof of this embodiment is 5-100 nm; the diameter of the aramid pulp and the fibrillated PAN fibers is 0.5-1 μm, and the length is 10-1000 microns; the diameter of the PI fibers is 6 μm, and the length is 3 mm; the thickness of the prepared lithium battery separator is 20 μm, the porosity is 71%, the air permeability is 40s / 100cc, and the mechanical strength is 48Mpa.
[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium battery separator, characterized in that: The lithium battery separator is formed by stacking a skeleton fiber layer, a nanofiber layer and a polymer network layer from bottom to top; the skeleton fiber layer is interwoven with micron fibers and chemical short fibers, the nanofiber layer is interwoven with nanofibers, and the polymer network layer is interwoven with polymers; the nanofibers partially extend into the skeleton fiber layer, and the polymer partially extends into the nanofiber layer; The preparation method of the lithium battery separator comprises the following steps: 1) adding water and a dispersant to disperse the micron fibers and chemical short fibers uniformly to obtain a skeleton fiber slurry, and forming a skeleton fiber layer; 2) adding water and a dispersant to the nanofibers to disperse them uniformly to obtain nanofiber slurry; then depositing the nanofiber slurry on the skeleton fiber layer to form a nanofiber layer, and obtaining a wet film after filtering and squeezing; 3) Mixing the polymer and the organic solvent and stirring them evenly to obtain an oil phase polymer solution; spraying the oil phase polymer solution onto the surface of the nanofiber layer of the wet film, the organic solvent quickly leaves and dissolves with water, the polymer precipitates into a network, and forms a polymer network layer on the surface of the wet film, which is then sent to an oven for baking to volatilize the organic solvent and water to obtain a lithium battery separator.
2. A lithium battery separator according to claim 1, characterized in that: The diameter of the nanofiber is 5-100 nm; the diameter of the micron fiber is 0.5-1 μm, and the length is 10-1000 μm; the diameter of the chemical short fiber is 1-6 μm, and the length is 1-12 mm.
3. A lithium battery separator according to claim 1, characterized in that: The nanofiber is at least one of nano-aramid fiber, nano-cellulose fiber, nano-polyacrylonitrile fiber, and fibrillated Tencel fiber; the micron fiber is at least one of fibrillated chemical staple fiber, pulp, and micron cellulose fiber; the chemical staple fiber is at least one of PET fiber, PAN fiber, PBO fiber, PA fiber, PI fiber, and aramid staple fiber.
4. A lithium battery separator according to claim 1, characterized in that: The polymer is at least one of aramid, polyacrylonitrile, polyvinylidene fluoride and polymethyl methacrylate.
5. A lithium battery separator according to claim 1, characterized in that: The lithium battery separator has a thickness of 10-70 μm, a porosity of 45-75%, an air permeability of <50 s / 100 cc, and a mechanical strength of 10-100 Mpa.
6. A lithium battery separator according to claim 1, characterized in that: In step 2), the membrane is filtered and squeezed until the moisture content is 35-80%, and then transferred to a dry blanket to obtain a wet membrane.
7. A lithium battery separator according to claim 1, characterized in that: The ratio of the sum of the amounts of the micron fibers and the chemical short fibers, the amount of the nanofibers, the amount of the polymer and the dispersant is 30-70:20-80:1-20:0.1-2.
8. A lithium battery separator according to claim 1, characterized in that: The content of chemical short fibers in step 1) is 0.6-1 kg / m 3 ; Step 2) The content of nanofibers in the nanofiber slurry is 2-4kg / m 3 ; In step 3), the content of the polymer in the oil phase polymer solution is 10-30% 。 9. A lithium battery separator according to claim 1, characterized in that: The dispersant is any one of sodium carboxymethyl cellulose, polyacrylamide, polyethylene oxide, and sodium hexametaphosphate; the organic solvent is any one of NMP, acetone, tetrahydrofuran, DMF, DMA, TEP, DMSO, DMAc, and butanol sulfone.
Citation Information
Patent Citations
Lithium-sulphur battery diaphragm preparation method, lithium-sulphur battery diaphragm and lithium-sulphur battery
CN107230764A
Lithium battery diaphragm
CN211743278U
Separator, separator-electrode composite and electrochemical device comprising the same
KR1020160054936A
Single fiber layer structure of micron or NANO fibers and multi-layer structure of micron and NANO fibers applied in separator for battery
US20140162110A1